Impact of vegetation cover on climate change in different regions of Iraq - Wedyan G. Nassif; Farant H. S. Lagenean; Osama T. Al-Taai (Caspian Journal of Environmental Sciences)
Vegetation determines the percentage of soil covered with green vegetation. Spatial and temporal changes of vegetation occur in the same year due to plant cycle, crop harvesting, animal grazing, and plant pruning. Vegetation areas can be divided into five main types: forest, grassland, tundra, desert, and ice cover. Climate, soil, the soil's water-holding capacity, and the slope or angle of the land determine the types of plants that will grow in a particular area. Relative humidity is the amount of moisture in the air at a given temperature compared to what the air can hold at that temperature. The air is not able to hold onto the water vapour, since it is moving so fast. To understand the expected changes in the climatic elements of the atmosphere and water, alterations in the behaviour of temperature, relative humidity, and vegetation cover were studied. Four stations were used over Iraq extending from north to south. The reason for choosing these stations is due to the difference in climatic changes and also, the geographical nature plays an important role in determining the difference of these variables from one region to another and other weather phenomena. We obtained average monthly and annual temperatures, dew point, and relative humidity during 1988-2018 for selected stations in Iraq from the European Centre for Medium-range Weather Forecast. Several results were reached, including that the highest value of vegetation cover for four selected stations during the study period recorded in Baghdad station was more than 0.9, and the lowest value observed in Basra station was less than 0.4. The highest relative humidity value was recorded in the Mosul Station where it covered 69% in the northern and central regions of the country specifically in the winter season, and 18% in the western regions of the Rutba Station in the spring and autumn, in addition, 13% in the southern regions in the summer as seen in the Basra Station. We note that the maximum temperatures were recorded in the summer in July and August due to evaporation in these areas as they are of a dry or semi-arid nature, reaching 55 ºC, while the lowest value in the Mosul station in December and January, since this area enjoys green plants and forests and precipitation. When using Spearman's test, it was found that the strength of the correlation is strong between relative humidity and vegetation cover and the relationship is positive between them. In contrast, the relationship between vegetation cover and temperature, the relationship is inverse and the strength of the correlation is weak to medium. Finally, it was found that the spring and autumn are characterized by dense vegetation cover, and this period is important for plant growth due to the availability of appropriate weather and environmental conditions.